The Role of Students in History Learning at School: From Memorizing Facts to Historical Thinking and Meaning-Making in Life - Adi Wiranata; Johan Setiawan; Bahtiar Afwan; Meyke Garzia; Sinta Meilya Ulfah (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
History learning in schools still faces challenges related to low student interest and engagement due to the dominance of rote memorization approaches. This condition limits the development of students’ critical thinking skills and their ability to interpret historical values in everyday life. This article aims to examine the role of students in history learning at school, particularly in the paradigm shift from memorizing historical facts toward developing historical thinking and meaningful life interpretation. This study employs a library research approach by analyzing relevant literature on history education, learning interest, and students’ historical thinking skills. The findings indicate that active student involvement through contextual learning, historical literacy, and critical reflection can enhance learning motivation and foster historical thinking abilities. Students are not only able to understand past events but also to relate them to contemporary social realities. Therefore, history learning should be designed in a student-centered manner to become more meaningful, relevant, and contributive to character formation and national awareness in accordance with the demands of 21st-century education.